Mutation in the mitochondrial 12S rRNA gene in two families from Mongolia with matrilineal aminoglycoside ototoxicity. Issue 2 (February 1997) - Pandya, A; Xia, X; Radnaabazar, J; Batsuuri, J; Dangaansuren, B; Fischel-Ghodsian, N; Nance, W E
Abstract : Irreversible hearing loss is a catastrophic complication of treatment with aminoglycoside antibiotics such as streptomycin, gentamycin, and kanamycin. Many kindreds showing a matrilineal pattern of inheritance of this trait have been described in China where the widespread use of aminoglycoside antibiotics accounts for approximately 25% of profound deafness in some districts. Because of the characteristic inheritance pattern, mitochondrial DNA (mtDNA) mutations were postulated to be the cause of the deafness in these pedigrees. In 1993 it was shown that an A to G substitution at base pair 1555 of the mitochondrial 12S ribosomal RNA gene was the only mutation common to all the families with aminoglycoside ototoxicity. We ascertained three Mongolian pedigrees from the School for the Deaf and Blind in Ulaanbaatar, all of which contained multiple affected subjects with streptomycin induced deafness in a pattern consistent with matrilineal transmission. Amplified mtDNA, obtained from transformed lymphoblastoid cell lines using previously described primers, showed the A to G point mutation in the 12S rRNA gene in two of the three families by restriction analysis as well as direct sequencing. No other example of this substitution was found among 400 control samples from Mongolians with normal hearing. We have thus confirmed the clinical relevance of the 1555 A to G mitochondrial mutation in the 12S rRNA gene by identifying it in affected subjects with familial aminoglycoside ototoxicity in another ethnic group. In countries where aminoglycosides are widely used, genetic counselling and screening of high risk families before the use of these drugs could have a dramatic effect on the incidence of deafness.